High connectivity across the fragmented chemosynthetic ecosystems of the deep Atlantic Equatorial Belt: efficient dispersal mechanisms or questionable endemism?. Issue 18 (9th August 2013) - Teixeira, Sara; Olu, Karine; Decker, Carole; Cunha, Regina L.; Fuchs, Sandra; Hourdez, Stéphane; Serrão, Ester A.; Arnaud‐Haond, Sophie
Abstract: Chemosynthetic ecosystems are distributed worldwide in fragmented habitats harbouring seemingly highly specialized communities. Yet, shared taxa have been reported from highly distant chemosynthetic communities. These habitats are distributed in distinct biogeographical regions, one of these being the so‐called Atlantic Equatorial Belt (AEB). Here, we combined genetic data (COI) from several taxa to assess the possible existence of cryptic or synonymous species and to detect the possible occurrence of contemporary gene flow among populations of chemosynthetic species located on both sides of the Atlantic. Several Evolutionary Significant Units (ESUs) of Alvinocarididae shrimp and Vesicomyidae bivalves were found to be shared across seeps of the AEB. Some were also common to hydrothermal vent communities of the Mid‐Atlantic Ridge (MAR), encompassing taxa morphologically described as distinct species or even genera. The hypothesis of current or very recent large‐scale gene flow among seeps and vents was supported by microsatellite analysis of the shrimp species Alvinocaris muricola / Alvinocaris markensis across the AEB and MAR. Two nonmutually exclusive hypotheses may explain these findings. The dispersion of larvae or adults following strong deep‐sea currents, possibly combined with biochemical cues influencing the duration of larval development and timing of metamorphosis, may result in large‐scale effective migration among distant spots scattered on the oceanic seafloor. Alternatively, these results may arise from the prevailing lack of knowledge on the ocean seabed, apart from emblematic ecosystems (chemosynthetic ecosystems, coral reefs or seamounts), where the widespread classification of endemism associated with many chemosynthetic taxa might hide wider distributions in overlooked parts of the deep sea.